A critical review on the development of metal-organic frameworks for boosting photocatalysis in the fields of energy and environment. (20th January 2022) - Swetha, S.; Janani, B.; Khan, S. Sudheer
Abstract: Metal-organic frameworks (MOFs) are a distinct class of porous, crystalline materials with excellent photocatalytic activity. These inorganic-organic hybrids have gathered much attention because of their unique properties such as high surface area, vast structural diversity, pore surface characteristics, modifiable framework morphology and semiconductor nature. The synergistic effect provided by the customisable building blocks of MOFs has made them ideal candidates for designing versatile photocatalysts with superior performance. Hence, it becomes vital to present a glance of the recent breakthroughs in the development of various MOF-based photocatalysts to improve the pullbacks in this research area. This review gives an overall picture of the diverse range of MOF-based photocatalysts. The strategies that have been adopted to boost their photocatalytic activity such as post-synthetic modification (PSM), heterojunction designing, doping, introduction of co-catalysts, ligand or substituent functionalization, modulation of metal-oxidation state and bandgap engineering also been explained. Further, the review focuses on the early research developments, structural diversity, synthesis methods, cleaner production and the recent developments in MOF-based photocatalysts for various photocatalytic applications including hydrogen production, CO2 conversion, photodegradation, photo electrochemical reaction (PEC), oxygen evolution reaction (OER) and fabrication of MOF-derived compounds. Finally, the futuristic challenges and scopes of MOFs as photocatalysts have been discussed. Graphical abstract: Image 1 Highlights: MOFs based photocatalysts for environmental remediation and clean energy production. The strategies to boost their photocatalytic performance are explained. Photocatalytic applications such as CO2 conversion, H2 production, etc are critically reviewed. The futuristic challenges and research gaps in this area are discussed.